The effectiveness of Information and Communication Technologies (ICTs) in teaching and learning in high schools in Eastern Cape Province - OA Ojo; EO Adu (South African Journal of Education, 2018)
The effectiveness of the use of information and communication technologies (ICTs) in teaching and learning is germane to the recent educational innovations in South Africa. The study examined the level of availability and utilisation of ICT facilities by teachers and students in high schools in Eastern Cape Province, South Africa as well as the factors influencing and challenging its effectiveness. A random sampling technique was adopted to select a sample of 600 (450 students and 150 teachers) for the study. Four research questions were answered with the aid of self-developed instruments tagged Teachers’ Questionnaire on Effectiveness of ICTs in Teaching and Learning (TQEICTTL) and Students’ Questionnaire on Effectiveness of ICTs in Teaching and Learning (SQEICTTL). Frequency and a simple percentage were used to analyse the data obtained. It was revealed that the highest available ICT facilities in all selected schools were mobile phones being used by students to download relevant information on their various courses and exchange ideas and knowledge among other students. It was, therefore, recommended that government play an active role in the effectiveness of the use of ICTs by funding ICTs in schools through training and re-training of teachers and exposure of stakeholders to the relevance of the pedagogy relating to the use of ICTs for teaching and learning.